OH reactivity measurements during OASIS Barrow field intensive Spring 2009 (Arctic Data Center, 2016)
A measurement intensive campaign was carried out in Barrow, Alaska in spring 2009 as part of the Ocean Atmosphere Sea Ice Snowpack (OASIS) program. This dataset contains OH reactivity measurements from that campaign. The data file is ASCII text, comma delimited. OH reactivity was measured using a flow tube injector system with Chemical Ionization Mass Spectrometry (CIMS). OH is produced via photolysis of water by an Hg lamp in an injector rod and then introduced to ambient air in a glass flow tube. A complete decay is measured in 2.5 min with units of s^-1. Ambient air was sampled from a height of 2 m above ground level. The level of detection is 2 s^-1, with an uncertainty of plus or minus 25%.